Society-related Fears and Personal Mental Health - Mutz, Michael; Justus Liebig University Giessen (My University, 2024)
This paper explores the relationship between society-related fears and personal mental health. Respondents of an online survey representing the German population (18 + years) answered how much they are worried about eight societal developments (armed conflicts, social inequality, rise of right-wing extremism, crime and terror, immigration, climate change, artificial intelligence, pandemics). The analysis demonstrate that the sum score of society-related fears is significantly associated with higher levels of anxiety and depression. Particularly concerns about poverty, digitalization and pandemics are associated with higher anxiety and depression scores. Further explorations show that specific fears are intermingled with political ideologies, i.e. people fear different societal developments according to their ideological standpoints. Politically left-leaning individuals regard climate change and rising right-wing extremism as more threatening, while politically right-leaning individuals’ fears relate more strongly to migrants, terror and crime. The fears with the largest negative effect on mental health are poverty and armed conflicts for individuals who identify as left and digitalization for individuals who identify as right. Overall, findings lend support to the general notion that the world’s current ‘polycrisis’ is highly relevant and generally detrimental for mental health and human wellbeing.
Keywords: ddc:796